2019
DOI: 10.1111/1365-2435.13287
|View full text |Cite
|
Sign up to set email alerts
|

Variation in plant functional traits is best explained by the species identity: Stability of trait‐based species ranking across meadow management regimes

Abstract: It is commonly assumed in trait‐based studies that plant functional traits are species‐specific, being more variable among species than among different environmental conditions. If the environment affects traits, it is assumed that species react in a similar direction and conserve the functional distances. The rank of species based on the trait values is then unchanged, which justifies the use of species trait averages from database values. Such assumptions of species specificity are, however, increasingly dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Anthropogenic nutrient enrichment, either via airborne deposition or climate warming inducing the release of nutrients from soil organic matter, is a major cause of biodiversity loss and shifts in plant community composition worldwide (Boutin et al., 2017; Stevens, 2019; Tilman et al., 2001). In experimental studies, nutrient addition has also been shown to modify intraspecific traits, for example, to enhance plant height, SLA, foliar N content and leaf greenness (Mudrák et al., 2019; Tatarko & Knops, 2018). These are traits related to rapid growth in resource‐rich conditions (Reich, 2014; Wright et al., 2004) and they are therefore likely to confer greater performance and competitive ability under nutrient‐rich conditions (Carmona et al., 2019; Suding et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic nutrient enrichment, either via airborne deposition or climate warming inducing the release of nutrients from soil organic matter, is a major cause of biodiversity loss and shifts in plant community composition worldwide (Boutin et al., 2017; Stevens, 2019; Tilman et al., 2001). In experimental studies, nutrient addition has also been shown to modify intraspecific traits, for example, to enhance plant height, SLA, foliar N content and leaf greenness (Mudrák et al., 2019; Tatarko & Knops, 2018). These are traits related to rapid growth in resource‐rich conditions (Reich, 2014; Wright et al., 2004) and they are therefore likely to confer greater performance and competitive ability under nutrient‐rich conditions (Carmona et al., 2019; Suding et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Data on functional traits of our study species were compiled from various sources (listed in Table 1). Clonal and architectural traits were extracted from the CLOPLA database (Clonal plants Database; Klimešová et al , 2017), leaf traits are from on‐site, using mostly a single measurement campaign in 2013 (for detail see Mudrák et al , 2019), and seed and dispersal traits are older measurements from the site (Stachová, 2005). For the analyses, species trait values were averaged over all the treatments and a single value per species was used.…”
Section: Methodsmentioning
confidence: 99%
“…We are grateful to the authors of Mudrák et al (2019) (Ondřej Mudrák, Jiří Doležal, Alena Vítová) and many students participating in the 2013 trait measuring campaign, and all the students assisting with vegetation recording and experiment maintenance during the years. We thank Francesco de Bello for his feedback on previous versions of the paper and Nichola Plowman for revision of our English.…”
Section: Acknowledgementmentioning
confidence: 99%
“…Köhler et al, 2005;Doležal et al, 2018;Tonn et al, 2019). Recently, a great emphasis is placed on the examination of ecological mechanisms shaping the community composition (see review in Mudrák et al, 2019), and thus on the exploration of the community assembly rules (Maire et al, 2012;Hedberg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Řezníčková, 2007;Kącki and Michalska-Hejduk, 2010) and to more general management issues (e.g. Schaffers, 2002), while studies examining the functional diversity of Molinia meadows are sparse (but see Mudrák et al, 2019).…”
Section: Introductionmentioning
confidence: 99%